Customers Preferences Towards Shariah Compliant Products And Services: The Case Study Among Academician and Non-Academician in Higher Education Institutions (HEIs) in Pahang - Rashidi, Abbas; Mohd Rizuan, Abd Kadir (Jabatan Kemajuan Islam Malaysia (JAKIM), 2013)
The purpose of this paper is to examine the main factors that influence customers to deal with Shariah compliant products and services particularly in a dual banking environment in Pahang. This study, presents primary data collected by self-administered questionnaires involving a sample of 240 academician and nonacademician in Higher Education Institutions (HE!s) in Pahang, which sets out to establish a ranking of the various factors which influence their bank selection decision and seek to determine homogeneous academician and non-academician are in relation to their Shariah product selection decision. The factors are analyzed using t-test. Statistical Package for Social Services (SPSS) was employed for this analysis. This study reveals that the selection of Shariah compliant products and services appears to be predominantly a combination between quality services and the lower service charges by bank. More significant differences were found when academicians were compared with non-academician in Shariah product selection decision.